The Diversity of Plankton in Sangihe – Sangir Talaud Islands, Sulawesi, Indonesia - Hikmah Thoha; Nurul Fitriya (Fakultas Biologi | Universitas Jenderal Soedirman, 2010)
The research of Oceanographical Expedition was conducted on May 2009. Research Vessel of Baruna Jaya VIII was used to accommodate the research team, which is a part of the EWIN ( Widya Nusantara Expedition) project with a topic of discovering the ultimate frontier of Indonesia and strengthening our national resilience, such as survival, energy, and natural resources, food, disaster, and health. This paper shows plankton research with environment studies, such as temperature and salinity. Plankton was sampled using Kitahara Net with mesh size of 80 µm for phytoplankton and Norpac Plankton Net with mesh size of 300 µm for zooplankton. The sample was poured into a bottle with formalin of 4% as preservative from 13 stations. The results showed that the phytoplanktons consist of 22 diatom genera and 10 dinoflagellates. The phytoplankton abundance was due the flourishing of Chaetoceros sp., Rhizosolenia sp., Nitzschia sp., and Thalassiothrix sp. Ceratium sp. and Protoperidinium sp., Pyrocystis sp., and Cyanobacteria Trichodesmium sp. were common among the dinoflagellates. The zooplanktons consist of 30 taxa, the group of which are mostly composed of Copepoda, Calanoida, Cyclopoida, Oikopleura, and Chaetognata. Environmental studies were also discussed.